Optimasi Parameter Mesin Cnc Wirecut Terhadap Waktu Pemotongan Dengan Metode Taguchi Analysispada Material H13 - Bayu Wiro Karuniawan, Ali Imron (Techno Bahari, 2017)
CNC Wirecut machine is one of the non-conventional machining which can cutting complex shape. The cutting results are more accurate and precision, smooth but the cutting process spend more time in processing. The research uses steel H13 by using experimental design with orthogonal matrix L8(27). The process parameters are low power, arc off time, interaction of low power and arc off time, feedrate override, wire tension, water flow, which every parameter has two levels. Optimization in this research using Taguchi Analysis Method and the response that observed are cutting time. The response has characteristics Smaller is Better quality. The results of Taguchi analisys indicates that the most contribution of parameters are Low power 78.18%, Feedrate override 4.93%, Wire tension 16.27%. While Arc off time, Interaction of low power and arc off time, Water flow effect is not significant. Optimization of cutting time responses are Low power (LP) is 10 Watt, Arc off time (AFF) is 50 seconds, Feedrate override (FR) is 5 mm/sec, Wire tension (WT) is 15 N, Water flow (WF) is 7 kg/cm2.